BIOLOGICAL MATURATION AND SEDENTARY BEHAVIOR IN CHILDREN AND ADOLESCENTS: A SYSTEMATIC REVIEW - Eliane Denise Araújo Bacil; Thiago Siva Piola; Priscila Iumi Watanabe; Michael Pereira da Silva; Rosimeide Francisco Santos Legnani; Wagner de Campos (Journal of Physical Education)
ABSTRACT The aim of this study was to analyze the association between biological maturation and sedentary behavior in children and adolescents. We performed a systematic review in May 2015 in the PubMed/MEDLINE, SportDiscus, Web of Science and LILACS databases, with no restriction of time. A total of 294 potentially relevant articles were identified and seven met the inclusion criteria. A direct association was identified between sedentary behavior and tempo of biological maturation. Sedentary behavior appears to increase with advancing chronological and biological age in both genders. Regarding the relationship between sedentary behavior and timing of biological maturation, greater sedentary behavior was observed in early maturing boys and girls. However, in some studies, this relationship varied between genders. Biological maturation appears to contribute to the increase in sedentary behavior in children and adolescents.